The Development and Evolution of Digital Leadership: A Bibliometric Mapping Approach-Based Study - Karakose, Turgut; Kocabas, Ibrahim; Yirci, Ramazan; Papadakis, Stamatios; Ozdemir, Tuncay Yavuz; Demirkol, Murat (Mdpi, 2022)
The inevitable digitalization of workplaces in the present era, generally as a result of technological developments, has caused a paradigm shift, along with new innovative business models and business behaviors, which has required leaders to possess certain digital skills for sustainable corporate performance. Hence, studies on digital leadership have attracted the attention of academics and practitioners worldwide, with many studies having been conducted on the topic. However, a comprehensive analysis of the intellectual architecture, knowledge structure, and thematic evolution of the digital leadership field of research using science mapping tools has yet to be conducted. The current study, therefore, aimed at reviewing the intellectual structure and evolution of the digital leadership field through a bibliometric and science-mapping analysis. This study used digital leadership as an umbrella term comprising leadership styles such as e-leadership, virtual leadership, technology leadership, and leadership 4.0, which have similar meanings and can be used interchangeably. With this purpose, bibliometric performance and science mapping analysis was performed on articles related to the research field that were retrieved from the Scopus database using SciMAT software (version 1.1.04). The results of the study revealed that the scope of digital leadership research is gradually expanding and diversifying and that publication output is increasing steadily. In addition, period-based analysis showed that the technology management theme during the first period, the virtual teams and technology themes during the second period, and the COVID-19, virtual reality, and digital technologies themes during the third period emerged as the motor themes and formed the focus of research in this field. Thematic evolution analysis showed that virtual leadership during the first and second periods, virtual teams during the second period, e-leadership and technology during the second and third periods, and digital leadership, COVID-19, and virtual reality during the third period, along with technology leadership in all three periods were all noteworthy as well-developed research themes. These findings enable a better understanding of the research field of digital leadership and provide a reference for future research by revealing the conceptual structure and thematic evolution of the digital leadership knowledge base.
Keywords: digital leadership; technology leadership; e-leadership; virtual leadership; leadership 4; 0; bibliometric analysis; science mapping; SciMAT